PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER RELIGIUS SISWA DI MTS SWASTA DARUL ILMI PANGKALAN BRANDAN - Sri Agustini; Zaifatur Ridha; Utari Ramadhani; Windi Khairunnisa (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2023)
This study aims to determine how the role of Islamic religious education teachers in shaping the religious character of students through extracurricular activities Tahfidz Quran. The problem of teachers in forming students' religious character regarding the challenges of the world of education, students having broad intellectual intelligence is an obligation that must be possessed. However, education in Indonesia also prioritizes students' emotional intelligence, one of which is through the formation of religious characters in students. The formation of this religious character can be done in various ways including through extracurricular activities at school. This type of research is a qualitative research with a descriptive analysis approach. The informants of this study were Islamic religious education teachers, school principals and students who were involved in extracurricular activities. Methods of data collection through interviews, observation and documentation. The data analysis technique used is triangulation of data sources. The results of this study indicate that Islamic religious education teachers play a role in helping the formation of student character through habits such as self-reflection, Tahajud prayer, habituation of praying on time and giving advice about the personality of a memorizer of the Al-Quran. Through these habits, religious values ​​begin to form in students. This result was obtained through collaboration between Islamic religious education teachers and the school who jointly gave the best contribution in the formation of student character.